1981
DOI: 10.1002/ajh.2830100115
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia vera in identical twins

Abstract: The occurrence of polycythemia Vera in family members has been a rare event, with little or no documentation in the literature to suggest a common genetic defect. We report here on the first case of polycythemia Vera documented in identical twins. No chromosomal abnormalities have yet been detected in these patients. The criteria for the diagnosis of polycythemia Vera are reviewed, and the possible implications of our findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…[11][12][13][14][15] In a recent French study, 16 the authors described 72 families and indicated that, as suggested by previous observations, 1,17,18 JAK2 (V617F) is an acquired somatic mutation in a portion of patients with familial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] In a recent French study, 16 the authors described 72 families and indicated that, as suggested by previous observations, 1,17,18 JAK2 (V617F) is an acquired somatic mutation in a portion of patients with familial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Before the discovery of JAK2 (V617F) mutations, few reports of families with CMD with a clinical phenotype mimicking sporadic CMD have been reported [90][91][92][93][94]. In detail, a study of six families with familial PV revealed an autosomal dominant inheritance with incomplete penetrance and excluded a linkage between PV phenotype and a number of candidate loci (9p, 20q, 13q, 5q, MPL, EPOR) [90].…”
Section: Genetic Background Of Familial Cmdmentioning
confidence: 99%
“…Reports of PV in monozygotic twins and increased rate in family members hint at some genetic in¯uence [11,12]. Our patient's family members were asymptomatic and complete blood count tests were all normal.…”
Section: Discussionmentioning
confidence: 69%